2021
DOI: 10.1021/acsnano.1c04242
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Core–Shell Resonance Harvester for Application of Artificial Cochlea Based on the Piezo-Triboelectric Effect

Abstract: The demand for flexible, efficient, and self-powered cochlear implants applied to remedy sensorineural hearing loss caused by dysfunctional hair cells remains urgent. Herein, we report an acoustic core–shell resonance harvester for the application of artificial cochleae based on the piezo-triboelectric effect. Integrating dispersed BaTiO3 particles as cores and porous PVDF-TrFE as shells, the acoustic harvest devices with ingenious core–shell structures exhibit outstanding piezo-triboelectric properties (V oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…[607][608][609][610][611] Moreover, a sensor with a hybrid mechanism can also offer complementary and improved performance. [612][613][614] For example, when piezoelectric sensing is coupled with piezoresistive sensing, a wider detection range can be obtained. 615-617 (6) In addition to developing sensors with excellent performance, signal identification and signal analysis are key steps to implement when using those devices towards practical applications.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…[607][608][609][610][611] Moreover, a sensor with a hybrid mechanism can also offer complementary and improved performance. [612][613][614] For example, when piezoelectric sensing is coupled with piezoresistive sensing, a wider detection range can be obtained. 615-617 (6) In addition to developing sensors with excellent performance, signal identification and signal analysis are key steps to implement when using those devices towards practical applications.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…(b,f) Solution synthesis approaches (b) for preparing BaTiO 3 /PVDF-TrFE membranes with core–shell nanostructures to mimetic basilar membrane in cochlea (f). Images b and f reprinted from ref . Copyright 2021 American Chemical Society.…”
Section: Nanotechnology For Biomimetic Architecturesmentioning
confidence: 99%
“…Moreover, the organization of nanostructures could also impact the performance of materials. Zheng et al reported an artificial basilar membrane based on the piezotriboelectric effect . They applied a multistep procedure to incorporate BaTiO 3 nanoparticle cores into porous poly­(vinylidenefluoride- co -trifluoroethylene) (PVDF-TrFE) shells to fabricate a membrane with well-organized core–shell structures that can generate charge separation and a potential gradient under uniform pressure (Figure b,f).…”
Section: Nanotechnology For Biomimetic Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The demand for adaptable, efficient, and self-powered cochlear implants is still pressing. As shown in Figure 7A, Jiaqi Zheng et al proposed a cochlear implant based on the piezoelectric-triboelectric effect made of BTO and PVDF (Zheng et al, 2021). By dispersing the BTO nano powder in PVDF, a shell-core structure is formed that enhances the piezoelectric and triboelectric response.…”
Section: Self-driven Sensing Systemmentioning
confidence: 99%